2013
DOI: 10.1111/adb.12042
|View full text |Cite
|
Sign up to set email alerts
|

Involving the cerebellum in cocaine-induced memory: pattern of cFos expression in mice trained to acquire conditioned preference for cocaine

Abstract: Versión / Versió:Preprint Conflict of Interest (COI) StatementThe authors of the present manuscript declare no conflict of interest. AbstractDue to its capital role in drug seeking, consumption and addictive behaviour there is a growing interest in identifying the neural circuits and molecular mechanisms underlying the formation, maintenance and retrieval of drug related memories. Human studies focused on neuronal systems that store and control drug-conditioned memories have found cerebellar activations duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 62 publications
13
45
0
Order By: Relevance
“…As a matter of fact, the presence of dopaminergic synaptic components in the cerebellum of primates and rodents has been repeatedly demonstrated (Melchitzky and Lewis, 2000;Carbo-Gas et al, 2014a). This finding is consistent with the observed reciprocal connections between the cerebellum and the ventral tegmental area (VTA), the main source of dopamine in the mesocorticolimbic system (Ikai et al, 1992).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…As a matter of fact, the presence of dopaminergic synaptic components in the cerebellum of primates and rodents has been repeatedly demonstrated (Melchitzky and Lewis, 2000;Carbo-Gas et al, 2014a). This finding is consistent with the observed reciprocal connections between the cerebellum and the ventral tegmental area (VTA), the main source of dopamine in the mesocorticolimbic system (Ikai et al, 1992).…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, a plausible explanation for the cerebellar response during cue-elicited craving might be the previously identified role of the cerebellum in prediction (Carbo-Gas et al, 2014a;Miquel el al., 2016). This possibility is supported by theories on cerebellar function that involve this part of the brain in a generalized prediction process (Courchesne and Allen, 1997;D'Angelo and Casali, 2013).…”
Section: The Cerebellum's Role: Craving or Prediction?mentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, we have shown that conditioned preference towards an odour associated with cocaine was directly correlated with cFOS expression in cells at the dorsal region of the granule cell layer of the cerebellar vermis [21]. These findings are coincident with those of some clinical reports.…”
Section: Introductionsupporting
confidence: 83%
“…Nevertheless, it is a fact that addictive drugs, in a certain dose range, have the ability to elicit this approach response towards the stimulus that have been paired with (Carbo-Gas et al, 2014;Braida et al, 2004). MDPV also shows this effect.…”
Section: Resultsmentioning
confidence: 99%